Integrating Puzzle-Based Learning Activities into Arabic Reading Skills Instruction: A Development Study - Nur Hafsoh, Ummi; Inayah, Inayah; Sutiyono, Agus; Rahma Wati, Wiwit; Waesama-ae Waemamu, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study aimed to develop a broken text puzzle learning media to support Arabic reading skill learning on the at-taÊ¿Äruf topic for seventh-grade students at MTs Ar-Rois Cendekia Semarang. A research and development approach using the ADDIE model was employed, consisting of analysis, design, development, implementation, and evaluation stages. The media was validated by material, language, and media experts to assess its feasibility, while student responses were used to determine practicality and acceptance. Expert validation indicated that the media met the â€œvery feasibleâ€ criteria in terms of content, language, and visual design. Student responses showed a high level of engagement and positive perception, with the majority categorizing the media as very positive. The broken text puzzle integrates cooperative, game-based learning, encouraging students to arrange fragmented texts into coherent passages. The findings suggest that this interactive media can support reading comprehension and engagement, and provide a model for future research on innovative Arabic learning approaches.